Far-red LED light alters circadian rhythms and elicits dark-adapted ERG responses in rodents. - Xian Chen; Steven Kreuser; Dinesh Hirenallur-Shanthappa (PLoS ONE)
Rodents are assumed to be blind to red light, thus red light is often used in the dark phase of a light/dark cycle to facilitate study procedures using nocturnal rodents. However, effects of red light in dark phase on behaviors and circadian rhythms in rodents are not yet clear. Thus, we evaluated effects of various long wavelength red light-emitting diode (LED) light on circadian rhythm and electroretinogram (ERG) in C57BL/6J mice and Wistar Han rats. Animals were implanted with telemetry devices to measure body temperature, heart rate, blood pressure, and locomotor activity for circadian rhythm assessment. In contrary to infra-red light, all visible long wavelength red lights, including the far-red LED light with a peak at 741 nm, induced significant alterations in circadian rhythms and dark-adapted rod photoreceptor-mediated ERG responses in mice and/or rats. However, far-red light did not elicit light-adapted cone photoreceptor-mediated ERG responses in both mice and rats. These findings demonstrate that rodents can perceive all spectrum of long wavelength red lights that are visible to humans, and exposures of red lights in dark phase interfere with their circadian rhythms. A dim far-red LED with peak wavelength in the range of 740-760 nm is recommended to use in the dark phase of a rodent room, and potential impacts are considered when using red light >2 photopic lux.